Development of Electronic Module with Augmented Reality on Pyramid for VIII Grade - Evalia Nuryana; Atik Wintarti (Program Studi S1 Matematika UNESA, 2022)
In order to create a joyful learning environment, especially during a pandemic that requires learning to be carried out online, an innovation is needed such as the use of interactive learning media for mutual learning which can be accessed online. Electronic modules with Augmented Reality are packaged in the form of learning media that can be used independently everytime and everywhere. This study aims to develop an electronic module with android-based Augmented Reality named